2022
DOI: 10.3390/molecules27092755
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Antidepressant Action of Duloxetine Co-Administered with the TAAR1 Receptor Agonist SEP-363856 in Mice

Abstract: Here, we explored the possible interaction between duloxetine and SEP-363856 (SEP-856) in depression-related reactions. The results showed that oral administration of duloxetine showed powerful antidepressant-like effects in both the forced swimming test (FST) and the suspension tail test (TST). SEP-856 orally administered alone also exerted an antidepressant-like effect in FST and TST, especially at doses of 0.3, 1, and 10 mg/kg. In addition, duloxetine (15 mg/kg) and SEP-856 (15 mg/kg) both showed antidepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Recently, these findings were further corroborated by another group [68]. In this study, ulotaront decreased immobility time in both the FST and its analog, the tail suspension test, as well as the potentiated effects of the antidepressant duloxetine [68]. Moreover, ulotaront (15 mg/kg, p/o, for 21 days) mitigated modeled anhedonia-like states induced by chronic mild unpredictable stress in the sucrose preference test, with no effect in non-stressed mice [68].…”
Section: Other Effects Of Ulotarontsupporting
confidence: 59%
See 1 more Smart Citation
“…Recently, these findings were further corroborated by another group [68]. In this study, ulotaront decreased immobility time in both the FST and its analog, the tail suspension test, as well as the potentiated effects of the antidepressant duloxetine [68]. Moreover, ulotaront (15 mg/kg, p/o, for 21 days) mitigated modeled anhedonia-like states induced by chronic mild unpredictable stress in the sucrose preference test, with no effect in non-stressed mice [68].…”
Section: Other Effects Of Ulotarontsupporting
confidence: 59%
“…An analysis of ulotaront's effects in the forced swim test (FST), a routine animal test performed to estimate the antidepressant-like activity of pharmacological agents, revealed that administration of the compound (dose range: 1-10 mg/kg, p/o) resulted in a reduction in immobility time in mice, indicating that ulotaront may have some antidepressant-like action [17]. Recently, these findings were further corroborated by another group [68]. In this study, ulotaront decreased immobility time in both the FST and its analog, the tail suspension test, as well as the potentiated effects of the antidepressant duloxetine [68].…”
Section: Other Effects Of Ulotarontmentioning
confidence: 87%
“…In addition to the good isolated effect of Ulotaront, in combination with Duloxetine (5-HT and NE dual reuptake inhibitor), tests showed better results in experimental animals. Therefore, the synergy of TAAR1 and monoamines can be a powerful tool to improve AD action [ 96 ].…”
Section: The Family Of Taars—a New Target For Depression Therapy?mentioning
confidence: 99%
“…TAAR1 is being studied as a potential therapeutic target in the treatment of various mental disorders, such as schizophrenia [ 2 , 27 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Ulotaront (SEP-363856) is a TAAR1 agonist with 5-HT1A receptor agonist activity, currently being tested in phase III clinical development, with very promising results from the phase II trials, which led to the FDA designation as a breakthrough therapy for the treatment of schizophrenia [ 26 , 27 , 28 , 29 , 30 , 40 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…TAAR1 agonists can play a certain role in alleviating depression-like and anxiety-like behaviors in animal models [ 27 , 28 , 47 , 49 ]. Another report showed that SEP-363856 and duloxetine could have a significant antidepressant effect in a mouse forced swim test.…”
Section: Introductionmentioning
confidence: 99%